CORPORATE SECURITY AND SUSTAINABLE ENERGY DEVELOPMENT - Trbojević, Milovan; Svirčević, Branislav (National interest, 2025)
Sustainable energy development and corporate security have numerous interdependent and conditional correlation relationships. The importance of the research subject imposes the need to adequately present the correlation and causal relationship between energy availability and corporate security. Accordingly, the paper aims to synthesize existing scientific knowledge and draw new possible conclusions on the research subject. Also, the aim is to analyze the impact of energy on corporate security as a highly complex, multivalent, and multi-manifest phenomenon using a multidisciplinary approach. The above will create a foundation for raising awareness of the necessity of rational consumption of energy resources in the sphere of corporate business, as well as the need to introduce alternative or renewable energy sources. Corporate security and sustainable energy development have a common goal: to create a safe and stable environment for the functioning of economic and social systems. Sustainable energy development and corporate security have numerous interdependent factors that affect the complete financial, ecological, political, and social aspects of society, the state, and the wider international community. The aforementioned interdependence factors were examined using analytical and synthetic methods, of which content analysis, classification, and deduction are the most important and most frequently applied data collection and processing methods.